Controls on Ice Cliff Distribution and Characteristics on Debris‐Covered Glaciers. Issue 6 (24th March 2023) - Kneib, Marin; Fyffe, Catriona L.; Miles, Evan S.; Lindemann, Shayna; Shaw, Thomas E.; Buri, Pascal; McCarthy, Michael; Ouvry, Boris; Vieli, Andreas; Sato, Yota; Kraaijenbrink, Philip D. A.; Zhao, Chuanxi; et al.
Abstract: Ice cliff distribution plays a major role in determining the melt of debris‐covered glaciers but its controls are largely unknown. We assembled a data set of 37, 537 ice cliffs and determined their characteristics across 86 debris‐covered glaciers within High Mountain Asia (HMA). We find that 38.9% of the cliffs are stream‐influenced, 19.5% pond‐influenced and 19.7% are crevasse‐originated. Surface velocity is the main predictor of cliff distribution at both local and glacier scale, indicating its dependence on the dynamic state and hence evolution stage of debris‐covered glacier tongues. Supraglacial ponds contribute to maintaining cliffs in areas of thicker debris, but this is only possible if water accumulates at the surface. Overall, total cliff density decreases exponentially with debris thickness as soon as the debris layer reaches a thickness of over 10 cm. Plain Language Summary: Debris‐covered glaciers are common throughout the world's mountain ranges and are characterized by the presence of steep ice cliffs among the debris‐covered ice. It is well‐known that the cliffs are responsible for a large portion of the melt of these glaciers but the controls on their formation, development and distribution across glaciers remains poorly understood. Novel mapping approaches combined with high‐resolution satellite and drone products enabled us to disentangle some of these controls and to show that the ice cliffs are generally formed and maintained by the surface hydrology (ponds or streams) or by the opening of crevasses. As a result, they depend both at the local and glacier scale on the dynamic state of the glaciers as well as the evolution stage of their debris cover. This provides a pathway to better represent their contribution to glacier melt in predictive glacier models. Key Points: We derived an unprecedented data set of 37, 537 ice cliffs and their characteristics across 86 debris‐covered glaciers in High Mountain Asia We find that 38.9% of the cliffs are stream‐influenced, 19.5% pond‐influenced and 19.7% are crevasse‐originated Ice cliff distribution can be predicted by velocity, as an indicator of the dynamics and state of evolution of debris‐covered glaciers